Appraisal of toxic metals in water, bottom sediments and fish of fresh water lake - Javaria Muneer (Elsevier, 2022)
Lakes are most diverse and interactive ecosystems in the world. In this study physiochemical parameters were determined of Mangla Dam Lake which is in District Mirpur Azad Jammu and Kashmir (AJK). Concentrations of heavy metals such as Cd, Cr, Cu, Mn, Ni, Pb and Zn were determined in samples of water, sediment, muscle, gills, intestine, liver, and kidneys of fish of the study area. Water samples showed average pH 7.64, Turbidity 2.59 NTU, Conductivity 461 µm/cm, TDS 205 mg/L and Salinity 0.22 mg/L. Low dissolved oxygen of 3.43 mg/L is recorded here. The analyzed data was compared with the international guidelines. In water concentration of Cd > Pb > Zn > Ni > Cr > Mn > Cu. In sediment concentration of Mn > Cr > Zn > Ni > Cu > Cd > Pb. Heavy metal concentrations decreased in muscles as Cr > Zn > Pb > Cd > Mn > Cu > Ni. In gills Zn > Cr > Pb > Mn > Cd > Cu > Ni. In intestine, Zn > Cr > Cu > Mn > Pb > Cd > Ni. In liver, Zn > Cr > Cu > Pb > Mn > Cd > Ni. In kidneys Zn > Cr > Cd > Pb > Cu > Mn > Ni.